A Feasibility Study of Bumdes in the Bengkalis District (Case Study at BUMDES Unggul Sari, Wonosari Village) - Nanda, Juanda Ju; Maulana, Hutomo Atman (Politeknik Negeri Bengkalis, 2024)
BUMDES Unggul Sari is a business entity belonging to Wonosari Village, Bengkalis District, Bengkalis Regency, Riau Province that has business units, one of which is a savings and loan business unit. The savings and loan business unit at BUMDES Unggul Sari only provides loans to Wonosari Village residents with a minimal loan of IDR 5,000,000 and a maximal of IDR 60,000,000, with a minimal loan term of 1 year and a maximal of 5 years, where the length of the loan is determined based on the borrower's ability. The research results show that BUMDES Unggul Sari savings and loan business unit was declared viable financially with a Payback Period (PP) of 8.5 years (feasible). Net Present Value (NPV) IDR I71,672,418.77 (feasible). The Profitability Index (PI) 1,5 (feasible). However, the Internal Rate of Return (IRR) 11% MARR 13,25% the savings and loan business unit at BUMDES Unggul Sari is not oriented towards the benefits of BUMDES Unggul Sari management in terms of material, but rather to improve the economic development of MSMEs in Wonosari Village community. In this case, the researcher is neutral, and IRR is not the main factor in the feasibility study of the savings and loan business unit at BUMDES Unggul Sari..Keywords: feasibility, Â Payback Period(PP), Net Present Value (NPV), Internal Rate of Return(IRR), Profitability Index (PI)